The 21st century : mapeh in action 2 : worktext in music, arts, physical education, and health - Zabala-Hernandez, Ma. Karina Melody; Alcazar-Zabala, Nonita; Lacia, Gerardo C.; Limos, Adelina P.; Delos Reyes, Girly Grace L. (Sampaloc Manila : Rex Book Store, Inc., 2016)
"The 21st Century MAPEH in Action is a series of Music, Arts, Physical Education, and Health Education books for the Basic Education (Grade 1 to 10) students in the Philippines." This set of instructional materials is based on the philosophy, objectives, and list of learning competencies of the K to 12 Basic Education Program outlined by the Department of Education (DepEd). This worktext is based on the designed of the K to 12 MAPEH curriculum, which has the spiral progression of process, concepts, and skills. It is also grounded in performance-based learning. In addition, this worktext is strongly anchored on the combined, sound, conceptual frameworks of Differentiated Instruction and Differentiated Assessments. It is divided into the four content areas of this subject: /music, Arts, Physical Education, and Health Education. The first section is all about Music. It includes the elements of music: melody, harmony, rhythm, dynamics, tempo, forms, and styles from all continents and historical periods. The second section discusses Arts, and its various forms and elements. The third section includes a thorough discussion of concepts in Physical Education and a comprehensive presentation of physical fitness activities. The last section covers an in-depth discussion of Health Education and related health practices aimed to enlighten young people about the importance of appropriate health practices. Each section has four quarters that correspond to the four grading periods."
Includes glossary, references
English text